STRATEGIC ANALYSIS OF COMPETITIVENESS OF HIGH-TECH COMPANIES AS A TOOL FOR MANAGING THE REGION'S INNOVATIVE DEVELOPMENT - Doroshenko, Yuriy A.; Starikova, Mariia S.; Somina, Irina V.; Malykhina, Irina O.; Riapukhina, Viktoriia N. (Journal of Applied Engineering Science, 2019)
The sustainability of a high-tech business in a competitive environment which has been characterized by high turbulence is mainly due to its ability to adapt to changes that are already underway and anticipate future market transformations. Adaptability is a characteristic of an enterprise which gives  by its management system. However, it depends on the state and degree of variability of the competitive environment. Despite the diversity of properties of the competitive environment, in our opinion, its complex characteristic that influences the ability of HTC to maintain stability to external changes taking place is turbulence, which has the property of mobility, complexity, uncertainty. Taking into account the analysis of the concept under study in physics and aerodynamics, we can consider turbulence to be irregular in time with the randomness of the fluctuations of the parameters of the competitive HTC environment. Our methodology for evaluating of CSHTC is based on the principles of complementarily and congruence and is based on measuring the discrepancy between the planned and achieved results on the indicators that are crucial for the key product groups of a high-tech company. Testing methods carried out on the example of high-tech companies in the pharmaceutical sector of the Central Federal District of the Russian Federation.
Keywords: innovative development; environment; high-tech companies; competitiveness